Smart distributed embedded systems for healthcare applications - Nagrath, Preeti; Alzubi, Jafar; Singhla, Bhawna; Rodrigues, Joel 1972-; Verma, A. K. (CRC Press, 2023)
"The text covers new techniques that will be helpful for patient's early diagnosis of diseases and start treatments with the help of distributed technology. It will serve as an ideal reference text for graduate students and researchers in diverse engineering fields including electrical, electronics and communication, computer, and biomedical"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Medical informatics; Artificial intelligence -- Medical applications; Artificial intelligence; Computer networks; Virtual reality; Medical Informatics Applications; Artificial Intelligence; Electronic Health Records -- organization & administration; Computer Communication Networks; Virtual Reality; Médecine; Informatique; Intelligence artificielle en médecine; Intelligence artificielle; Réseaux d'ordinateurs; Réalité virtuelle; artificial intelligence; virtual reality; Artificial intelligence; Medical applications